Visual social marketing for dummies - Neher, Krista (John Wiley & Sons, 2014)
It's no secret that visual content online really draws in viewers. People love Pinterest, Facebook, and the like for visual sharing and engaging. Smart marketers know their companies need to tap into this, but where and how to start? Visual Social Marketing For Dummies offers a clear roadmap for creating effective, well-defined visual social marketing strategies as part of your overall marketing and social media plans. From defining goals to developing highly visual content across a range of social media platforms, this book is the perfect step-by-step guide to get you there.